Efficient macrocyclization for cyclicpeptide using solid-phase reaction - Kim, J; Hong, IK; Kim, HJ; Jeong, HJ; Choi, MJ; Yoon, CN; Jeong, JH (PHARMACEUTICAL SOCIETY KOREA, 2002)
Cyclicpepticles are important targets in peptide synthesis because of their interesting biological properties. Constraining highly flexible linear peptides by cyclization is one of the mostly widely used approaches to define the bioactive conformation of peptides. Cyclic peptides often have increased receptor affinity and metabolic stability over their linear counterparts. We carried out virtual screening experiment via docking in order to understand the interaction between HLE-Human Leukocyte Elastase and ligand peptide and to identify the sequence that can be a target in various ligand peptides. We made cyclic peptides as a target base on Met-IIe-Phe sequence having affinity for ligand and receptor active site docking. There are three ways to cyclize certain sequences of amino acids such as Met-IIe-Phe-GIy-IIe. First is head-to-tail cyclization method, linking between N-terminal and C-terminal. Second method utilizes amino acid side chain such as thiol functional group in Cys, making a thioether bond. The last one includes an application of resin-substituted amino acids in solid phase reaction. Among the three methods, solid phase reaction showed the greatest yield. Macrocyclization of Fmoc-Met-IIe-Phe-GIy-Iie-OBn after cleavage of Fmoc protection in solution phase was carried out to give macrocyclic compound 5 in about 7% yield. In the contrast with solution phase reaction, solid phase reaction for macrocyclization of Met-IIe-Phe-Gly-IIe-Asp-Tentagel in normal concentrated condition gave macrocyclic compound 7 in more than 35% yield.
Keywords: CONFORMATIONAL-ANALYSIS; CYCLIC-PEPTIDES; AMINO-ACIDS; COMBINATION